Investigation of Trade Interactions Effect of North Sumatera with Malaysia and Singapore: An Application of Autoregressive Distributed Lag (ARDL) Model - Rudi Gunawan, Sya’ad Afifuddin, Sirojuzilam, Rahmanta (International Journal of Advanced Science and Technology, 2020)
The purpose of this study is to investigate of trade interaction of North Sumatera province with the nearest countries, namely Malaysia and Singapore. The analytical model used in this study is the Gravity model through export destination countries (Malaysia and Singapore) and uses time-series data from 1983 to 2016. The results show that there was a long-term (cointegration) relationship derived from the variables used. By using the long-term coefficient, this study showed that North Sumatera's gross regional domestic product indicator, Malaysia's gross domestic product, North Sumatera's economy, Malaysia's economy, Singapore's population, and exchange rate have a major relationship with two neighboring countries on North Sumatera's trade interaction. Also, Singapore's gross domestic product indicator has no major relationship with North Sumatera's trade interaction. The study found that the highest change speed value (ECt-1) returned to the equilibrium point was 62 percent negative. It means that the positive impact of North Sumatra's trade interaction with Malaysia and Singapore on North Sumatera, Indonesia's export and economic growth